Emerging innovations in ICTs - Rurangirwa, David; Addom, Benjamin K. (Technical Centre for Agricultural and Rural Cooperation, 2013)
The conference will help to address the ‘inclusive' component of ICT4Ag, or the idea that no one will be left out. It is imperative that emerging innovations support rather than exclude stakeholders in the agricultural sector